The Impact of National Health Insurance (JKN) Participation, Access to Health Services, and Economic Factors on the Poverty Depth Index in Central Java Districts/Cities - Desiana Tri Hidayati; Dimas Bagus Wiranatakusuma (UNIVED Press, 2026)
The National Health Insurance Program (Jaminan Kesehatan Nasional/JKN) is Indonesia's strategic commitment to achieving Universal Health Coverage (UHC) and reducing health-related financial risks that can deepen poverty. While existing studies have examined the impact of JKN on healthcare utilization and out-of-pocket expenditures, its combined effects with healthcare access and local economic conditions on poverty intensity remain underexplored, particularly at the sub-national level. This study analyzes the impact of JKN coverage, healthcare access, and key economic factors on poverty depth across districts and cities in Central Java, Indonesia. A quantitative approach with a balanced panel data design was used, covering 35 districts/cities in Central Java from 2019 to 2024 (210 observations). Data are sourced from BPJS Kesehatan (active JKN membership), Statistics Indonesia (BPS) for the poverty depth index (P1), economic growth, and unemployment rate, and the Ministry of Health (community health center ratio). The analysis uses a fixed-effects regression model to control for heterogeneity that does not change over time, with robustness checks for model specification. JKN coverage has a significant negative effect on the poverty depth index (β = -0.0152, p<0.01), confirming its role in reducing poverty intensity. This effect is significantly strengthened in districts with better physical access to health facilities, as indicated by the negative and significant interaction term (JKN × Puskesmas: β = -0.0083, p<0.05). Economic growth shows a stronger poverty reduction effect (β = -0.0321, p<0.01), while the unemployment rate exacerbates poverty depth (β = 0.0264, p<0.01). JKN effectively contributes to reducing poverty depth, but its impact depends on adequate health infrastructure. Sustainable poverty reduction requires an integrated policy approach that combines health system strengthening through the simultaneous expansion of financial protection and physical access with broader economic strategies that stimulate inclusive growth and job creation. Policymakers should prioritize context-specific interventions that address both health sector and macroeconomic determinants of well-being.